2019
DOI: 10.1093/ofid/ofz038
|View full text |Cite
|
Sign up to set email alerts
|

Physical Functioning Among Patients Aging With Human Immunodeficiency Virus (HIV) Versus HIV Uninfected: Feasibility of Using the Short Physical Performance Battery in Clinical Care of People Living With HIV Aged 50 or Older

Abstract: Background The Short Physical Performance Battery (SPPB) is a well regarded physical functioning assessment including balance, gait speed, and chair-stand tests. Its use has not been widely assessed in human immunodeficiency virus (HIV) care. We evaluated the feasibility of integrating the SPPB into care of aging people living with HIV (PLWH) and compared SPPB performance with aged HIV-uninfected individuals. Methods We enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 25 publications
3
16
2
Order By: Relevance
“…The most altered component of the SPPB test was the 5STS as observed in middle-aged PLHIV in western countries [9,10] and in older PLHIV [21,22]. PLHIV needed more time to complete the test than controls [22] but less than the nearly 20-year older controls [21].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The most altered component of the SPPB test was the 5STS as observed in middle-aged PLHIV in western countries [9,10] and in older PLHIV [21,22]. PLHIV needed more time to complete the test than controls [22] but less than the nearly 20-year older controls [21].…”
Section: Discussionmentioning
confidence: 94%
“…Recent publications in older PLHIV from western countries reported similar results for the SPPB performance. In PLHIV aged 50 years or above living in the United States, it was reported a similar mean score (10.3 to 10.7) [ 21 , 22 ], a score similar to nearly 20-year older controls [ 21 ]. Another study in female PLHIV reported that 20% of them performed poorly with a median score of 11, but they discussed the possibility of a ceiling effect because of the participant’s age in their sample (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations